2001
DOI: 10.1039/b103614a
|View full text |Cite
|
Sign up to set email alerts
|

Control on the organized structure of monoalkylethylenediamine copper(ii) coordinated bilayer membranes by counter ions

Abstract: The organized structure of Cu 2+ -coordinated bilayer membranes formed by monoalkyl derivatives of ethylenediamine can easily be modulated by varying the counter ions, and their physical properties change correspondingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Monoalkyldiamines are structurally similar to alkylamines, and hence are pH responsive. They are readily coordinated with heavy metal ions such as Cu 2+ or Co 3+ strongly due to the two amino groups presented in their hydrophilic part, [30][31][32][33][34] which have important applications in industry as oating chemicals. Compared to the pH sensitivity, the properties of the ligands have rarely been addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoalkyldiamines are structurally similar to alkylamines, and hence are pH responsive. They are readily coordinated with heavy metal ions such as Cu 2+ or Co 3+ strongly due to the two amino groups presented in their hydrophilic part, [30][31][32][33][34] which have important applications in industry as oating chemicals. Compared to the pH sensitivity, the properties of the ligands have rarely been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the pH sensitivity, the properties of the ligands have rarely been addressed. 12,13,35,36 Studies are mainly focused on the metal ion induced vesicle formation, [30][31][32][33][34] whereas the effect of the species distribution caused by the ionization equilibria has oen been neglected in vesiculation. It has been demonstrated that micelles and vesicles can be formed in dodecyldiamine aqueous solutions at acidic and basic conditions, respectively, regardless of the spacer length between the two amino groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that N -amino groups can coordinate with transition metal ions, such as Cu 2+ , Co 2+ , Ni 2+ , Ag + , etc., to form metal complexes, owing to the ion pair electrons of N atoms, thereby resulting in some novel physicochemical properties. Figure shows the photographs of a typical transition induced by CuCl 2 in C 16 NP aqueous solution, in which the optically transparent solution of 0.04 mol/L C 16 NP at pH 6.1 transforms into a turbid solution upon adding equivoluminal 0.02 mol/L CuCl 2 aqueous solution, which is generally observed in other C m NPs (Figure S7 of the Supporting Information). Cryo-TEM results confirm the CuCl 2 -induced rodlike micelle (Figure a) to vesicle (Figure b) transition, and the size distributions measured by DLS also support the transitions (Figure S8a of the Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
“…Among these interactions, only the last one is specific and reversible. It was reported that the higher-level self-assemblies of lipid vesicles were obtained through bilayer-DNA , or bilayer-actin complexation, metal-ion complexation, and biotin-streptavidin molecular recognition . However, little work was performed on the transition between these structures.…”
Section: Introductionmentioning
confidence: 99%